2020
DOI: 10.7554/elife.52760
|View full text |Cite
|
Sign up to set email alerts
|

The inner junction complex of the cilia is an interaction hub that involves tubulin post-translational modifications

Abstract: Microtubules are cytoskeletal structures involved in stability, transport and organization in the cell. The building blocks, the α- and β-tubulin heterodimers, form protofilaments that associate laterally into the hollow microtubule. Microtubule also exists as highly stable doublet microtubules in the cilia where stability is needed for ciliary beating and function. The doublet microtubule maintains its stability through interactions at its inner and outer junctions where its A- and B-tubules meet. Here, using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 1,325 publications
(73 citation statements)
references
References 66 publications
3
67
0
Order By: Relevance
“…Lastly, we examined the inner junction region. Previous studies showed structural differences between Tetrahymena and Chlamydomonas in this region (Khalifa et al, 2020;Ma et al, 2019). Our modeling study confirmed this.…”
Section: Chlamydomonassupporting
confidence: 90%
See 4 more Smart Citations
“…Lastly, we examined the inner junction region. Previous studies showed structural differences between Tetrahymena and Chlamydomonas in this region (Khalifa et al, 2020;Ma et al, 2019). Our modeling study confirmed this.…”
Section: Chlamydomonassupporting
confidence: 90%
“…These differences are likely underlain by their unique molecular composition and structure (Satir et al, 2008). Previous studies have revealed marked differences in the cilia structure among different model organisms (Carvalho-Santos et al, 2011;Khalifa et al, 2020;Lin et al, 2014;Nicastro et al, 2011;Pigino et al, 2012). However, many comparisons were descriptive and were limited by the resolution of the structures.…”
Section: Chlamydomonasmentioning
confidence: 99%
See 3 more Smart Citations